Деякі зауваження з приводу інтерпретації археологічного матеріалу - Кузін-Лосєв, В.І. (Археологія, 1995)
Продовжуючи дискусію у журналі «Археологія», у статті наголошується на підходах, що існують у семіотиці для з'ясування того місця, яке посідали елементи культури в загальному її просторі. В статье рассматривается методология интерпретации археологических источников. В частности, отталкиваясь от положения семиотики о существовании в одной культуре нескольких не до конца взаимопереводимых самостоятельных систем, археологические культуры эпохи бронзы рассматриваются как содержащие в себе тексты с традиционной семантикой и тексты с порождающей семантикой. Учет подобного явления, как представляется автору статьи, позволяет избежать негативных последствий при определении семантически значимых элементов культуры и семантически нейтральных. Attention is paid to the methods of interpretation of archaeological sources. In particular, coming from the principles of semiotics on several not ultimately inter-translated independent systems in one culture, archaeological cultures of the bronze epoch are considered as such with engendering semantics. Taking into account this phenomen it is possible, in the author’s opinion, to avoid negative after-effects in identification of semantically significant and semantically neutral elements of culture.